ANALISIS HUBUNGAN KARAKTERISTIK PERUSAHAAN DENGAN PEMILIHAN METODE DEPRESIASI : PENERAPAN PSAK NO. 16 (AKTIVA TETAP) DAN PSAK NO. 17 (AKUNTANSI PENYUSUTAN) - Hendrawati Hendrawati (Fakultas Ekonomi Universitas Borobudur, 2014)
This study aimed to test the significant relationship between the size of the company, company profiles and industry types with depreciation methods. The sarnple in this.tudy is a publicly traded company that is listed on the Jakarta Stock Exchange (JSE) as many as 63 companies. The method used in this study is aimed at sampling (purposive sampling), one type of sampling aims (purposive sampling) used in this study was a purposive sample (judgment sampling). Collecting data using secondary sources (books, journals, and other literature that is still associated with the title). Contingency coefficient or Contingency Coefficient (C) is used to test the hypothesis and the results showed that (1) there is no significant relationship bet-ween firm size variable with variable depreciation method, (2) there is no significant relationship between the variables of company profiles with variable depreciation method, and (3) there is no significant relationship between the variable types of industries with variable depreciation method. Keywords: company size, company profiles, industry types, methods of depreciation.